Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Rumah Sakit Ortopedi Prof. Dr. R. Soeharso Surakarta) - Nugrahanto, Faizal Dwi, Ahmad Mardalis, S.E., M.B.A (2015)
This study aims to determine (1) the effect of leadership on employee performance. (2) the effect of the work environment on employee performance. (3) the influence of leadership and work environment on employee performance. (4) more variables affect the performance of employees at the Prof. Dr. R. Soeharso Orthopaedic Hospital of Surakarta. This type of research is quantitative. The sample in this study were employees at Prof. Dr. R. Soeharso Orthopaedic Hospital of Surakarta 100 respondents with a sampling technique Non-Probability Sampling. Methods of data collection using the questionnaire. Data analysis techniques that multiple regression analysis, t-test, F-test, and coefficient of determination (R2). The results showed there is a partial effect between the independent variables on the dependent variable. F-test data analysis is known there are significant variables simultaneously leadership and work environment to variable employee performance. While the regression coefficient indicates that the variable influential leadership is more dominant than the work environment on employee performance. Keywords: leadership, work environment, employee performance